THE INFLUENCE OF ZIKIR EDUCATION ON ALTRUISM BEHAVIOR THROUGH THE STUDENTS’ EMOTIONAL INTELLIGENCE IN THE LOMBOK ISLAND - Irhas, Irhas (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Objective: This study aims to examine the effect of dhikr education on altruistic behavior, with emotional intelligence as a mediating variable. Method: The method used is mixed methods, with a population consisting of mursyid, tarekat administrators, leaders of congregation groups, and students at the Darul Falah Pagutan Islamic Boarding School and the Qamarul Huda Bagu Islamic Boarding School, totaling 998 people, with a sample of 200 people. Data were collected through observation, interviews, questionnaires, and documentation, and analyzed qualitatively and quantitatively using SEM-PLS. Results: The results showed that dhikr education had a positive effect on altruistic behavior and emotional intelligence, with a coefficient of dhikr education on altruistic behavior of 0.219 and a t-statistic of 3.258, and an effect on emotional intelligence of 0.347 with a t-statistic of 6.170, both significant. In addition, emotional intelligence was also proven to influence altruistic behavior with a coefficient of 0.198 and a t-statistic of 2.694. Conclusion: Overall, dhikr education significantly contributes to increasing altruistic behavior through strengthening emotional intelligence, indicating a positive causal associative relationship between the three variables studied. Implications: The implication is that dhikr education can be used as a strategic approach to improve the moral and social quality of Islamic boarding school students, as well as the importance of integrating emotional intelligence in the religious education process. This can be applied in teaching programs at Islamic boarding schools and other educational institutions to encourage better character development, as well as increasing individual contributions to society through higher altruistic behavior.